Private sector and clusters development for agricultural transformation in Africa - Ulimwengu, John M.; Jenane, Chakib (Alliance for a Green Revolution in Africa, 2019)
This chapter looks at how agri-based clusters can be nurtured for further growth in the context of Africa and how they can drive private sector investment and innovation for agricultural transformation. It briefly describes the different types of agri-clusters, analyzes experience from developing these models around the world and lessons learned (successes and failures) from these. The chapter also proposes key factors to be considered by policy makers for clusters development to help Africa unleash the full potential of its agriculture sector.